Micro-mechanical investigation about degradation of grain boundary cohesive strength of neutron-irradiated stainless steels. Issue 10 (3rd October 2022) - Miura, Terumitsu; Fujii, Katsuhiko; Fukuya, Koji; Seto, Hitoshi
ABSTRACT: Degradation of grain boundary (GB) cohesive strength due to neutron irradiation is a possible factor causing IASCC. In order to clarify the dose dependence and degradation factors of GB cohesive strength of neutron-irradiated stainless steels, micro-tensile testing and microstructural analysis by transmission electron microscopy were conducted on individual GBs of neutron-irradiated stainless steels that were harvested from flux thimble tubes (FTTs) irradiated up to 73 dpa and a baffle former bolt (BFB) irradiated to 19 dpa. The micro-tensile specimens fabricated from the FTTs that included a GB showed higher intergranular fracture susceptibility at higher doses, while the change in susceptibility was small at intermediate doses. On the other hand, the micro-tensile specimen that was fabricated from the BFB had less intergranular fracture susceptibility than the FTT specimen of a similar dose. Fine cavities were confirmed both in matrix and on GBs of the FTTs, whereas they were not found on GBs of the BFB. Considering the present results and those from a previous study investigating effects of helium on GB fracture, it was concluded that the GB cavities degraded GB cohesive strength. However, other factors were possibly promoting intergranular fracture of neutron-irradiated stainless steels such as GB segregation. GRAPHICAL ABSTRACT: uf0001